Insight into Email-Based Data for Knowledge Discovery - Rathi, Dinesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The study provides an insight into email data including different elements that are present in email-based data such as headers, signature, confidentiality note, and attachments and their percentage share (in megabytes) in the overall data. The findings will give better understanding of the overall noise space in email-based data. Cette étude met en lumière les données de courriels, y compris différents éléments contenus dans les courriels, par exemple l’en-tête, la signature, les notes de confidentialité et les pièces-jointes, ainsi que le poids (pourcentage, en mégaoctets) par rapport au volume total d’information. Les résultats permettront une meilleure compréhension du bruit dans les données courriel.